1985
DOI: 10.1111/j.1365-2885.1985.tb00934.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of phenobarbital and primidone in canine epilepsy: a comparison

Abstract: The efficacy of phenobarbital and primidone against canine epilepsy was compared in a controlled study. Thirty-five dogs showing generalized tonic-clonic seizures (grand mal), treated for a minimum of 6 months, were included in the study; fifteen of these were treated with phenobarbital, the other twenty with primidone. Both drugs were dosed according to the clinical requirement; the daily doses ranged from 5-17 mg/kg phenobarbital and from 17-70 mg/kg primidone. The plasma concentrations of phenobarbital, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 3 publications
1
90
0
3
Order By: Relevance
“…Variable monotherapy efficacy for seizure reduction was evaluated in 8 studies for a total of 311 dogs 29, 30, 31, 32, 33, 34, 35. Twenty or more dogs were evaluated in each of 5 studies31, 32, 33, 34, 35 evaluating a total of 289 dogs treated from 5 to 32 months in 3 of the studies31, 32, 35 with undocumented duration in 2 studies29, 33 The cumulative success rate of >50% seizure reduction to improve seizure control was 82% (258/311 dogs), with a cumulative seizure‐free rate of 31% (93/311) and failure rate (no improvement) of 15% (48/311).…”
Section: Which Drug Should Be Used First?mentioning
confidence: 99%
See 3 more Smart Citations
“…Variable monotherapy efficacy for seizure reduction was evaluated in 8 studies for a total of 311 dogs 29, 30, 31, 32, 33, 34, 35. Twenty or more dogs were evaluated in each of 5 studies31, 32, 33, 34, 35 evaluating a total of 289 dogs treated from 5 to 32 months in 3 of the studies31, 32, 35 with undocumented duration in 2 studies29, 33 The cumulative success rate of >50% seizure reduction to improve seizure control was 82% (258/311 dogs), with a cumulative seizure‐free rate of 31% (93/311) and failure rate (no improvement) of 15% (48/311).…”
Section: Which Drug Should Be Used First?mentioning
confidence: 99%
“…Forty percent of the dogs became seizure‐free during treatment with phenobarbital compared to only 25% with primidone. Furthermore, primidone was less well tolerated in dogs than phenobarbital 30. In a retrospective trial in 65 epileptic dogs, primidone and phenobarbital were reported to exert similar efficacy, but important details of study design were not reported 43.…”
Section: Which Drug Should Be Used First?mentioning
confidence: 99%
See 2 more Smart Citations
“…28 Although there are limited available efficacy data regarding PB in cats, the efficacy of PB in epileptic dogs is reported to be between 60%-80%. 29 The most common adverse effects of PB reported in dogs are sedation, weight gain, increased thirst, increased urination, and increased appetite, most of which resolve within a few weeks of starting treatment. 30 In the author's experience, cats are less likely to develop polyuria and polydipsia when receiving this medication.…”
Section: Symptomatic Therapymentioning
confidence: 99%